‘Peace, Peace and Rumours of War’ - Ward, W. R. (The journal of ecclesiastical history, 2000)
Nationaler Protestantismus und Ökumenische Bewegung. Kirchliches Handeln im Kalten Krieg (1945–1990). By Gerhard Besier, Armin Boyens and Gerhard Lindemann (postscript by Horst-Klaus Hofmann). (Zeitgeschichtliche Forschungen, 3.) Pp. vi+1074. Berlin: Duncker & Humblot, 1999. DM 86. 3 428 10032 8; 1438 2326This is indeed a formidable offering – three and a half books by three and a half authors, all for the price of one and a half – and it must be admitted to those whose stamina or German quail at the prospect that some of the viewpoints and a little of the material by two and a half of the contributors has been made available in English in Gerhard Besier (ed.), The Churches, southern Africa and the political context (London 1999) at £9.99. The soft option is, however, no substitute for the real thing, which, like that other blockbuster, the late Eberhard Bethge's Bonhoeffer, is a contribution both to scholarship and to a struggle inside the German Churches. This, readers in the Anglo-Saxon world need to assess as best they can. It is not often that attempts are made by both the World Council of Churches and their principal paymasters in the German Churches to stop the publication of a work of scholarship, to be foiled (in best nineteenth-century style) by the liberalism of the German Ministry of the Interior; but that has happened here. And the rest of the world has the more reason to be grateful to the ministry for the authors have exploited the archives of the Stasi and the KGB, access to the latter of which has now been closed under pressure from the Russian Orthodox Church, which appears to have more to hide than anyone.The link between all this and Besier's inquiries in America is provided by the sad fate of the Protestant Churches of the Ost-Block during the Cold War.